A alocação de slots e a concorrência no setor de transporte aéreo - Cravo, Beatriz Malerba (2014)
This paper analyzes the regulatory history of the airline industry and the state control exercised through regulatory policies over the decades. Evaluation of the current access to the necessary infrastructure for the air transport service and its barriers to entry, notably the rules for allocation of slots. Analysis of different possibilities for the allocation of slots so as not to limit competition in the industry and ensure access for new entrants to the market: slot swap, odds, lines and primary auction. The allocation of slots in Brazil reflects the past history of the airline industry, and there is not a solution that harmonizes perfectly with the interests of airlines companies already consolidated with the fostering of competition. This paper analyzes the different possibilities, indicating the contribution of each to a more competitive environment, as well as its disavantages vis a vis the scenario already consolidated in the industry.